Effect of different rest intensities on time spent near maximal oxygen uptake during a decreasing high-intensity training session - a pilot study - Triska, C.; Soukup, C.; Scharner, M.; Milbert, P.; Ernst, J.; Mathy, A. (Journal of Science and Cycling, 2023)
Besides exercise economy, fractional utilization of maximal oxygen uptake (VO2max) and durability, VO2max is one of the four major parameters reflecting endurance exercise performance (Spragg, Leo, & Swart, 2023). In order to improve VO2max high-intensity interval training (HIIT) is commonly applied (Buchheit & Laursen, 2013). When more time is spent near VO2max during HIIT (e.g., 90% of VO2max) research has demonstrated larger improvements in VO2max. (Midgley & McNaughton, 2006). Various HIIT protocols have been assessed recently (for review: de Oliveira-Nunes, Castro, Sardeli, Cavaglieri, & Chacon-Mikahil, 2021), like a HIIT-protocol with decreasing duration of work as well as rest periods (Vaccari, Giovanelli, & Lazzer, 2020). Results of this research have demonstrated a longer time spent above 90% of VO2max compared to longer intervals (i.e., 4 min) and shorter intervals (i.e., 30 s). Most studies assessing the effects of HIIT on VO2max have modified intensity and duration of the work intervals, however, much less is known about modifying rest intensity. Therefore, the aim of this pilot study was to assess whether different rest intensities notably affect time spent near VO2max during an exhaustive HIIT-protocol.